Viability of automated collection of peripheral blood progenitor cells in a horse: report of procedure - Bernardo, J. O. [UNESP]; Escodro, P. B.; Notomi, M. K. [UNESP]; Roveri, E. G.; Gomes do Nascimento, T. (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2017)
The biotechnology used in tendon, bone and joint recoveries in Equine Medicine has improved in recent years. The most used are platelet rich plasma and stem cells from adipose tissue and bone marrow. However, recent studies have shown that stem cells can be found in the bloodstream, also named peripheral blood progenitor cells (CPP). This note aims at reporting the feasibility of automated collection of CPP in horses. The procedure was conducted in an equine, female, Quarter Horses, 2 years old, 385kg. The automated collection of CPP was conducted using apheresis equipment Fresenius-Kabi coupled to C4Y kit. The procedure lasted two hours and 30 minutes without complications, processing 5054mL of whole blood and obtaining 351mL of CPP. Upon completion of the collection, the content of CPP was separated into 10 ml aliquots and immediately stored at -18 degrees C. The automated technique proved to be feasible for horses, but needs improvement in order to achieve greater efficiency and reduce procedure time.
Keywords: horse; steam cells; peripheral blood progenitor cells